Numerical simulation of heat transfer in a large room with a working gas infrared emitter; Journal of Physics: Conference Series; Vol. 1675 : Thermophysics and Physical Hydrodynamics - Borisov B. V. Boris Vladimirovich; Kuznetsov G. V. Geny Vladimirovich; Maksimov V. I. Vyacheslav Ivanovich; Nagornova T. A. Tatiana Aleksandrovna; Gutareva N. Yu. Nadezhda Yurievna (2020, 2020)
Title screen